PENGASUHAN DAN PENANAMAN NILAI TERHADAP ANAK USIA DINI (TELAAH KOMUNIKASI KELUARGA: SUATU STUDI DESKRIPTIF) - Sari, Afrina (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2010)
This article discusses the cultivation of values that must be done by a nursemaid to the child she takes care of. There are two types of mothering models; one which is done by the mother herself at home and the other one that is conducted by a mothering assistant. The mothering model that uses an assistant can be done either by sending the child to a childcare institution or by hiring the assistant to work at home. Both the models are evaluated using family communication pattern in child mothering program. The method used in this writing is descriptive method with the secondary data taken from a library research.